الطبيعة القانونية لقرار تأديب الطبيب وأثرها على ضمانات المحاكمة التأديبية - سلخ، محمد لمين (جامعة الإخوة منتوري - قسنطينة 1, 2021)
نناقش من خلال هذه المداخلة، الطبيعة القانونية لقرار تأديب الطبيب الصادر عن مجلس أخلاقيات الطب المنعقد كهيئة تأديب، هل يعتبر قرار إداري أم قرار قضائي، وتأثير ذلك على توافر ضمانات المحاكمة التأديبية العادلة من عدمه، لا سيما طريقة الطعن فيه وأوجه الطعن، وكذا رقابة جهة الطعن عليه، وانعكاس ذلك على قواعد المسؤولية التأديبية للطبيب Abstract: Through this intervention, we discuss the legal nature of the physician disciplinary decision issued by the Medical Ethics Council convened as a disciplinary body, is it considered an administrative decision or a judicial decision, and the effect of this on the availability of guarantees of a fair disciplinary trial or not, especially the method of appeal against it and the aspects of appeal, as well as the supervision of the authority Appealing it, and its reflection on the rules of disciplinary responsibility of the doctor.
The Legal nature of disciplinary decision the doctor and their impact on the Disciplinary trial guarantees
مداخلة
Keywords: الطبيب; مجلس أخلاقيات الطب; المحاكمة التأديبية; الطعن بالإلغاء (الإبطال); الطعن بالنقض; The doctor; Medical Ethics Council; Disciplinary trial; Disciplinary decisions; Appeal to revoke a decision; Appeal to cassation